Ecoturismo no Brasil e desenvolvimento sustentável: casos de sucesso e desafios - Simoes, Octavio Matheus Paniguel (Universidade Federal de São Carlos, 2024)
This work investigates the relationship between sustainable development and ecotourism, highlighting how both promote sustainability through environmental conservation and the well-being of local communities. Focusing on the Brazilian context, the study aims to analyze successful cases of ecotourism in three regions: Bonito-MS, Brotas-SP, and Fernando de Noronha-PE, emphasizing their importance in protecting natural resources and promoting responsible practices that minimize negative impacts. Additionally, it seeks to identify the challenges facing the Brazilian ecotourism sector. Based on a literature review, the research identifies and discusses strategies that have proven effective in the success of ecotourism in these regions. Furthermore, the study addresses persistent challenges within the sector. The paper aims to contribute to the debate on sustainability in the tourism sector, offering valuable insights for academics, professionals, and policymakers interested in optimizing the benefits of ecotourism. Despite the progress made, this paper presents some gaps due to the fact that the topic is relatively recent and underexplored, with continuous development in the face of the vastness and diversity of ecotourism. Each location offers unique and innovative experiences that can be appreciated from various perspectives, providing unforgettable experiences and highlighting Brazil's great potential in the ecotourism landscape.
Ecotourism in Brazil and sustainable development: success cases and challenges
Keywords: Ecoturismo; Sustentabilidade; Desenvolvimento; Exemplos de sucesso de ecoturismo; Ecotourism; Sustainability; Development; Successful ecotourism examples; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA AGRARIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS